2010
DOI: 10.1186/1752-1947-4-130
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar soft part sarcoma of the tongue in a 3-year-old boy: a case report

Abstract: IntroductionAlveolar soft tissue sarcoma of the tongue is a very rare and aggressive tumor which occurs in infancy with a relatively controversial histogenesis. It may mimic benign vascular neoplasms and may metastasize to the lungs, brain or bones.Case presentationWe present the case of a three-year-old Caucasian boy who was admitted to our department with a history of dysphagia and two episodes of oral bleeding which had lasted for a period of six months. A thorough histological examination together with ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Despite the size of the tumor (>5 cm), there was no clinical mass and no facial deformity, which according to the literature should be a common sign (Table 1). 4, 5, 6, 7, 9, 10, 11, 12, 13, 14, 15, 16 It is also uncommon, only reported by Charrier et al, 10 that the tumor was very painful, and this is the first reported case with paresthesia of the lower lip.…”
Section: Discussionmentioning
confidence: 76%
“…Despite the size of the tumor (>5 cm), there was no clinical mass and no facial deformity, which according to the literature should be a common sign (Table 1). 4, 5, 6, 7, 9, 10, 11, 12, 13, 14, 15, 16 It is also uncommon, only reported by Charrier et al, 10 that the tumor was very painful, and this is the first reported case with paresthesia of the lower lip.…”
Section: Discussionmentioning
confidence: 76%
“…While in our analysis, we have found out an age range of 1.5-64 years with a mean of 18.25 ± 15.243 years. There were 31 (41.9%) males 9,10,15,16,23,25,[27][28][29][31][32][33][34][35][36] and 43 (58.1%) females 2,3,5,8,[11][12][13][14][16][17][18][19][20][21]24,26,27,[36][37][38][39][40][41][42][43][44][45][46] in the review and male-tofemale ratio of 1:1.4 with female predilection. Gender predilection in our review is in accordance with Wang et al 30 and male-to-female ratio is in contrast with that of Fanburg-Smith et al 16 According to Kim et al, 36 most of the patients were from the second decade with slender female predilection.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Esta neoplasia representa aproximadamente el 0,4-1 % de todos los casos de sarcomas de partes blandas y un 5 % de todos los sarcomas pediátricos de partes blandas. Durante las dos primeras décadas de vida, presenta cierta predilección por el género femenino y el sitio de origen más común es la región de cabeza y cuello, especialmente en la órbita y la lengua (Noussios et al, 2010).…”
Section: Melanoma De La Mucosaunclassified